Does the Environment Kuznets Curve Theory Exist in China? - Nikolaus Ekna Chandra Irawan (Universitas Negeri Semarang, 2023)
China's rapid economic growth has led to predictions that it will surpass the United States as the world's top economic power. However, this growth comes at the cost of increased emissions. The relationship between environmental degradation and income per capita is discussed through the Environmental Kuznets Curve (EKC) theory. A study conducted in China used variables such as GDP per capita, coal energy consumption, renewable energy consumption, and private sector domestic credit. The study utilized 31 years of time series data from 1991 to 2021 and employed the ARDL method for data processing. The findings suggest that the EKC hypothesis holds true in the short term, indicating an inverted U curve. However, in the long term, the EKC hypothesis does not hold. Coal energy consumption has a positive and significant impact on CO2 emissions in the long run. Similarly, renewable energy consumption shows a negative and significant effect on emissions in the long run. Private sector domestic credit has a positive and significant influence in the long run. It can be concluded that the EKC theory does not apply to China, and it is not possible to reduce emissions by simply improving the economy.